Coactosin-Like Protein in Breast Carcinoma: Friend or Foe? - Wang B; Zhao L; Chen D (Dove Medical Press, 2022)
Bei Wang,1 Limiao Zhao,1 Dandan Chen2 1Institute of Integration of Traditional Chinese and Western Medicine, the Hospital Affiliated to Jiangnan University, Wuxi, People's Republic of China; 2Department of Education, School of Humanities, Jiangnan University, Wuxi, People's Republic of ChinaCorrespondence: Bei Wang, Email xuewuhenwang@jiangnan.edu.cnBackground: Coactosin-like protein (COTL1) was first identified as protein that binds 5-lipoxygenase and F-actin; its functions in tumors remain unknown. COTL1 could inhibit the proliferation of breast cancer (BRCA) in vivo and in vitro; however, online public databases including UALCAN and Kaplan-Meier plotter showed high COTL1 expression in breast cancer tissue, which was correlated with poor prognosis. Therefore, we studied the role of COTL1 expression in human breast cancer and its use in determining clinical prognosis.Methods: We first used the UALCAN database and immunohistochemical analysis to elucidate COTL1 expression in BRCA. We then performed Kaplan-Meier plotting and immunohistochemical analysis to assess prognosis in BRCA in relation to COTL1 expression. Finally, we used the CancerSEA and LinkedOmics databases to evaluate the function of COTL1 in BRCA. The TIMER and TISIDB databases were used to evaluate the association between COTL1 expression and immune cell infiltration in BRCA.Results: UALCAN and immunohistochemical analysis showed that COTL1 was highly expressed in breast cancer. Furthermore, high COTL1 expression was correlated with poor prognosis in BRCA. We also found that COTL1 is involved in immune response via the CancerSEA and LinkedOmics databases. The TIMER and TISIDB databases showed that high COTL1 expression was correlated with immune cell infiltration.Conclusion: COTL1 expression was higher in breast cancer tissues than in normal tissues, and high COTL1 expression was correlated with poor prognosis and immune cell infiltration. These results provide a basis for the development of applications of COTL1 in determining the prognosis of breast cancer and its treatment.Keywords: COTL1, breast cancer, prognosis, Immune cell infiltration, biomarker